2016
DOI: 10.1080/08963568.2016.1226616
|View full text |Cite
|
Sign up to set email alerts
|

Client-based experiential learning and the librarian: Information literacy for the real world

Abstract: Business schools have increasingly turned to client-based experiential learning to better prepare their graduates with skills and abilities that translate to the workplace. The shift from academic learning to experiential learning requires a corresponding shift in the way librarians approach information literacy. This article explores this trend through the literature and through personal interviews and proposes ways in which library instruction, collection development, and liaison relationships can be tailore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…Typically, experiential activities (e.g., service learning, field experiences, internships) involve personal experiences that go beyond the classroom and allow students to observe and apply knowledge (York et al, 2010). Students are encouraged to seek out further connections by utilizing library resources that are directly relevant to the problem at hand by examining research reports as well as primary and secondary resources by bridging the gap between the classroom and the experiential activity (Spackman, 2016). When using library instruction in an Ancient Mediterranean Civilizations class, Dowling et al (2018) found that some students had only a basic understanding of what primary and secondary sources were, and students did not have an understanding of tertiary or fact-finding sources.…”
Section: Student Preferences For Teaching Methodsmentioning
confidence: 99%
“…Typically, experiential activities (e.g., service learning, field experiences, internships) involve personal experiences that go beyond the classroom and allow students to observe and apply knowledge (York et al, 2010). Students are encouraged to seek out further connections by utilizing library resources that are directly relevant to the problem at hand by examining research reports as well as primary and secondary resources by bridging the gap between the classroom and the experiential activity (Spackman, 2016). When using library instruction in an Ancient Mediterranean Civilizations class, Dowling et al (2018) found that some students had only a basic understanding of what primary and secondary sources were, and students did not have an understanding of tertiary or fact-finding sources.…”
Section: Student Preferences For Teaching Methodsmentioning
confidence: 99%
“…Se ha señalado, además, que los programas de educación de alta calidad en el campo de la administración deben incluir distintos formatos del aprendizaje experiencial como las prácticas de diferentes tipos, tanto en el aula convencional como a distancia, asignaturas diseñadas bajo el enfoque de Aprendizaje Servicio y espacios de formación, donde los estudiantes se relacionan con diversas industrias (Obi et al, 2021). En los contextos en los que se ha empleado el ae, se ha demostrado que predice de manera significativa el incremento en el nivel de compromiso de los estudiantes (Donovan & Hood, 2021), desarrollo de habilidades en el trabajo (Spackman, 2016) y desempeño general (Leal-Rodríguez & Albort-Morant, 2019).…”
Section: ¿Qué Es El Aprendizaje Experiencial?unclassified
“…Academic libraries have an extensive history of supporting experiential learning, whether through the framework of a competition or in a variety of other settings. This includes library support for internal initiatives like makerspaces and device lending (Barrett et al, 2018;Cross & Tucci, 2017;Rogers, Leduc-Mills, O'Connell, & Huang, 2015), as well as classroom-based activities like client-based design and active learning projects (Ishak & Ong, 2016;Spackman, 2016). Service learning, experiential learning that emphasizes civic engagement (Lim & Bloomquist, 2015), is both supported by libraries (Herther, 2008) and used by libraries to connect with their local communities (Heiselt & Wolverton, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%